QUALITY OF LIFE IN CHILDREN WITH DYSPHAGIA AND THEIR CAREGIVERS - Ilić Savić, Ivana (HEALTH CARE, 2024)
Dysphagia is defined as a swallowing disorder that can occur in all three phases of swallowing (oral, pharyngeal or esophageal). It is manifested as pain while swallowing, difficulty swallowing, feeling of food stuck in the throat or in the chest, heartburn, regurgitation of food and/or stomach acid, weight loss, hoarseness, etc. The primary aim of this study is to analyze the quality of life in children with dysphagia and their caregivers, while the secondary aim is to provide basic guidelines for improving the quality of their life. Data were collected by searching the following databases: PubMed, Google Scholar Advanced Search and Consortium of Serbian Libraries for Coordinated Purchase (Serbian: KoBSON). The review of previous research results has shown that children with dysphagia have a worse quality of life in comparison to their peers. Parents, who feel helpless because they cannot help their children, experience high levels of stress. Also, children with dysphagia lack the necessary support from the health system, and therefore, it is necessary to create guidelines to help children with dysphagia aimed at realizing their personal potentials in the functional, emotional and social domain.
Keywords: dysphagia, children, caregivers, quality of life, stress, guidelines